The Effect of Mathematical Literacy, Motivation and Student’s Independence toward Mathematical Problem Solving Ability - Meilani, Rina; Haji, Saleh; Sekarwinahyu, Mestika (FKIP Universitas Lampung, 2023)
Students' ability to solve mathematical problems is still low, students often experience obstacles in understanding problems so that they are less precise in choosing and using solving strategies from non-routine problems. There are many factors that influence this, so the purpose of this study is to assess several factors such as the influence of mathematical literacy on mathematical problem solving abilities, the effect of learning motivation on mathematical problem solving skills, the influence of independence on mathematical problem solving skills and the influence of mathematical literacy, motivation, and independence of the ability to solve mathematical problems. The method used is a quantitative method by making SMAN 1 Indralaya the object of research. The results of this study include mathematical literacy, learning motivation, learning independence and have a positive and significant effect on mathematical problem-solving abilities and the ability of the independent variables in this study to affect the dependent variable by 20.2%, while the remaining 79.8% is explained by variables other than variables independent in research.Keywords: mathematical literacy, motivation, independence, problem solving.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp275-290